Trading hot air: the influence of permit allocation rules, market power and the US withdrawal from the Kyoto Protocol - Gernot Klepper; Sonja Peterson (Kiel Institute for World Economics (IfW), 2002)
After the conferences in Bonn and Marrakech it is likely that international emission trading will be realized in the near future. Major influences on the permit market are the institutional detail, the participation structure and the treatment of hot air. Different scenarios do not only differ in their implications for the demand and supply of permits and thus the permit price, but also in their allocative effects. In this paper we discuss likely institutional designs for permit allocation in the hot-air economies and the use of market power and quantify the resulting effects with and without US partieipation by using the computable general equilibrium model DART
Keywords: C68; D58; F18; Q48; 330; hot air; permit allocation; market power; Kyoto Protocol; CGE Model; DART; emission trading; Emissionsrechte; Klimaschutz; Umweltabkommen; Allgemeines Gleichgewicht; Wirtschaftspolitische Wirkungsanalyse